The study of fluorescence enhancing and quenching effect of luminescent materials in sol gel for the detection of gases - Tee, Shiau Foon (2006)
The control of CO2, SO2 and O2 emission is important thus the determination of its concentration is important in many applications. This study is carried out to investigate and characterize the fluorescent properties of metal-chelate using fluorescent materials such as Î±-naphthoflavone (7, 8-benzoflavone), fluorescein and luminol. Initial investigation showed that Î±-naphthoflavone exhibit fluorescence at Î»em = 426 nm (Î»ex = 343 nm), fluorescein exhibit fluorescence at Î»em = 510 nm (Î»ex = 483 nm) and luminol at Î»em = 421 nm (Î»ex = 386 nm) at optimum pH 10.06, pH 8.90 and pH 8.62 respectively. The presence of CO2, SO2 and O2 were detected by Î±-naphthoflavone, fluorescein and luminol. Î±-naphthoflavone, fluorescein and luminol giving a non-linear change in the emission intensity with increase volume of SO2 and O2 gas. Therefore, Î±-naphthoflavone, fluorescein and luminol are not suitable for detecting SO2 and O2 gas. When dissolving CO2 gas into the complex, the emission wavelength (Î”Î»em) for fluorescein was shifted by 6 nm and luminol was 9 nm. The fluorescence properties of Î±-naphthoflavone, fluorescein and luminol entrapped in sol gel were also investigated. Results indicated that the emission intensity of the entrapped fluorescent material in sol gel decreased as compared to fluorescence in solvent. For the detection of CO2, the gas was bubbled onto the sol gel surface. It was observed that the emission intensity of Î±-naphthoflavone in sol gel increased linearly as the volume of CO2 gases increased. Meanwhile, fluorescein and luminol shows a non linear change with the increased CO2 amount in sol gel. Among the five metals ions that complex with Î±-naphthoflavone, fluorescein and luminol, it was found that the emission intensity of fluorescein-ferum complex decreases linearly after exposure to increasing amount of CO2 in sol gel giving a linear relationship with an equation was y = -7.2252 x + 271.01 and a correlation of 0.9234.